Minimally invasive coronary surgery - Todić, Mirko; Drljević-Todić, Vanja; Preveden, Andrej; Redžek, Aleksandar; Preveden, Mihaela; Zdravković, Ranko; Kalinić, Novica (Scripta Medica, 2021)
Minimally invasive options for coronary artery bypass graft (CABG) surgery progressed dramatically in the last decades. Minimally invasive CABG surgery is presented trough these forms: minimally invasive direct coronary artery bypass (MIDCAB), endoscopic atraumatic coronary artery bypass (EndoACAB), robot-assisted direct coronary artery bypass (RADCAB), total endoscopic coronary artery bypass (TECAB), and hybrid coronary revascularization (HCR). Unfortunately, these are still limited only to the specialised centres across the world, and haven’t been accepted by the majority of cardiac surgeons. A surgeon who is starting to practice minimally invasive CABG surgery needs to be ready for long duration of the interventions, higher rate of conversions to sternotomy, and significant learning curve. Great results that have been published on the subject of minimally invasive revascularisation methods support the potential of these alternative approaches to evolve in the near future.